GlowSafe Lunchbox: an early-warning innovation for food safety in school children - Kaniasan, Demaisuria; Ravi Kumar, Tishha; Prabu, Tulirmathii; Krisnan Murti, Sharane; Kumar, Nithyasri; Thanabalan, Divyamathi (2025)
The GlowSafe Lunchbox is a student-led innovation aimed at addressing food safety issues among schoolchildren. The device uses a saltwater-dried strip connected to a basic electrical circuit to detect the presence of unwanted moisture in a lunchbox, often a sign of leaking or spoiled food. When moisture is present, it completes the circuit and triggers a warning light. This extended abstract presents the rationale, methodology, findings, and implications of the GlowSafe Lunchbox project, which emphasizes early detection and low-cost design. Data were collected by testing various food items under controlled conditions. Results show consistent light activation with common moist foods, demonstrating its value as a practical early-warning tool. The study concludes that the GlowSafe Lunchbox offers a simple yet effective solution for enhancing food safety awareness in children.